"I tend to forget bad things": Immigrant and refugee young men's narratives of distress. (November 2019) - Hilario, Carla T; Oliffe, John L; Wong, Josephine P; Browne, Annette J; Johnson, Joy L
Distress among young immigrant and refugee men has drawn increasing research attention in recent years. Nuanced understandings of distress are needed to inform mental health and public health programming. The purpose of this research was to examine distress from the perspectives of young immigrant and refugee men living in Greater Vancouver, British Columbia, Canada. Thirty-three young men (aged 15–22 years) from diverse immigrant and refugee backgrounds participated in interviews, which were conducted between 2014 and 2015. Data were examined using narrative analysis and theories of masculinities. Three narratives were identified—norming distress, acknowledging distress as ongoing, and situating distress. The findings reveal that the narratives offer different frames through which distress was rendered a norm, or acknowledged and situated in relation to the participants' relationships and to masculine discourses that shaped their expressions of distress. The findings can inform initiatives aimed at providing spaces for diverse young men to acknowledge their distress and to receive support for mental health challenges.